Trends and variability of sea ice in Baffin Bay and Davis Strait, 1953–2001 - Stern , Harry L.; Heide-Jørgensen , Mads Peter (Polar Research, 2003)
The extent and duration of sea ice in Baffin Bay and Davis Strait has a major impact on the timing and strength of the marine production along West Greenland. The advance and retreat of the sea ice follows a predictable pattern, with maximum extent typically in March. We examine the area of sea ice in March in three overlapping study regions centred on Disko Bay on the west coast of Greenland. Sea ice concentration estimates derived from satellite passive microwave data are available for the years 1979–2001. We extend the record back in time by digitizing ice charts from the Danish Meteorological Institute, 1953–1981. There is reasonable agreement between the chart data and the satellite data during the three years of overlap: 1979–1981. We find a significant increasing trend in sea ice for the 49-year period (1953–2001) for the study regions that extend into Davis Strait and Baffin Bay. The cyclical nature of the wintertime ice area is also evident, with a period of about 8 to 9 years. Correlation of the winter sea ice concentration with the winter North Atlantic Oscillation (NAO) index shows moderately high values in Baffin Bay. The correlation of ice concentration with the previous winter’s NAO is high in Davis Strait and suggests that next winter’s ice conditions can be predicted to some extent by this winter’s NAO index.